Exploration of the improving effect of Cd-doping on structural, photocatalytic, and biological properties of ZnO nanoparticles - (:unkn) unknown (My University, 2023)
ZnO and cadmium (Cd)-doped ZnO (Zn1-xCdxO) nanoparticles with various compositions (0.0 ≤ x ≤ 0.8) were synthesized by sol-gel method. Structural, morphological, and photocatalytic properties as well as blood compatibilities of Zn1-xCdxO nanoparticles were investigated. While X-ray diffraction (XRD) applying the Rietveld refinement method was used to characterize the structural properties, scanning electron microscope (SEM) and transmission electron microscope (TEM) were used to investigate the surface morphology. It was found that the nanoparticles up to x < 0.03 Cd concentration had single phase of ZnO hexagonal wurtzite structure. Above x ≥ 0.03 Cd concentration, two phases (ZnO and cadmium oxide (CdO)) were observed. SEM images with different magnifications revealed the dense, quasi-spherical, and agglomerated morphology of Zn1-xCdxO nanoparticles. The elemental compositions of Zn1-xCdxO nanoparticles have also been studied by EDX analysis. The photocatalytic activities and blood compatibilities of Zn1-xCdxO nanoparticles were studied by the photocatalytic degradation tests of crystal violet (CV) and hemolysis tests and respectively. In the photocatalytic activity tests, two samples Zn0.90Cd0.10O and Zn0.80Cd0.80O stood out with photodegradation percentages of 69.9% and 72.8%. Among the Cd-doped nanoparticles, the Zn0.40Cd0.60O sample showed the highest blood compatibility with the weakest photocatalytic performance (degradation percentage; 32.2%). Structural properties, photocatalytic performance, and hemolytic potential of Zn1-xCdxO nanoparticles were investigated and compared with those of pure ZnO nanoparticles.
Keywords: Biyomedikal Mühendisliği; Matematik; Bilgisayar Bilimleri; Fizik; Atom ve Molekül Fiziği; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Mathematics; Computer Science; Physics; Atomic and Molecular Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MATEMATİK, UYGULAMALI; FİZİK, YOĞUN MADDE; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; MATHEMATICS; PHYSICS; MATHEMATICS, APPLIED; PHYSICS, CONDENSED MATTER; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Genel Kimya; Modelleme ve Simülasyon; Genel Malzeme Bilimi; Yoğun Madde Fiziği; Bioengineering; Physical Sciences; Atomic and Molecular Physics, and Optics; General Chemistry; Modeling and Simulation; General Materials Science; Condensed Matter Physics; Biomedical relevance; Hemolysis; Microstructure; Nanoparticle; Photocatalytic activity; Sol–gel